PERAN KEPOLISIAN DALAM HUBUNGAN KRIMINAL JUSTICE SYSTEM BERDASARKAN UNDANG-UNDANG NO. 8 TAHUN 1981 - Suhandi Suhandi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
Police Department is one part of criminal justice system in conducting police investigation to look for and find the suspects of the criminal then it is given feedback by arresting, jailing, and frisking as well as seizuring. The acts should be based on Decree Number 8 Year 1981 about Law Agenda on Crime to guarantee and protect human basic rights.